Bifacial sodium-incorporated treatments: Tailoring deep traps and enhancing carrier transport properties in Cu2ZnSnS4 solar cells. (September 2015) - Lin, Yi-Rung; Tunuguntla, Venkatesh; Wei, Shih-Yuan; Chen, Wei-Chao; Wong, Deniz; Lai, Chih-Huang; Liu, Ling-Kang; Chen, Li-Chyong; Chen, Kuei-Hsien
Abstract: Manipulating the nature of defects and carrier dynamics in kesterite Cu2 ZnSnS4 (CZTS) solar cells is challenging because of the complex behavior of defects. Among the various strategies used to reduce the defect levels, sodium-incorporated CZTS absorbers are effective and beneficial for defect passivation. In this study, we proposed a bifacial sodium-incorporated treatment (BSIT) in CZTS for the control of defect levels. The defect energy levels of the absorber measured by admittance spectroscopy decrease from 263 to 112 meV with increasing Na contents. In addition, impedance measurements of the sample after the BSIT showed an improved carrier dynamics with a prolonged minority carrier lifetime from 0.9 to 1.8 μs. This suggests that the post treatment of NaF diffused from the top and bottom surfaces of the CZTS absorbers is beneficial for carrier transport behaviors. Our results demonstrated that by manipulating the sodium content in the BSIT, defect passivation and effective reduction of carrier recombination can be attained, resulting in enhanced CZTS device performance from 4.1% to 5.6%. Graphical abstract: Highlights: Bifacial sodium incorporated treatment (BSIT) was evidenced as an effective strategy for defect passivation in CZTS solar cells. The manipulation of defect level energies in the CZTS:Na devices were applied for the investigation of sodium contents and passivated deep traps. Improved carrier transport dynamics including faster carrier detrapping rates and prolonged carrier lifetimes were achieved. The champion CZTS:Na device exhibits a 37% enhancement of power conversion efficiency from 4.1% to 5.6%.